PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN (STUDI PADA KONSUMEN HONDA BEAT PT. ASTRA HONDA MOTOR CABANG GAJAH MADA KOTA SEMARANG) - Nurul Lailatul Janah, 14.05.51.0039; Maskur, Ali (Students' Journal of Economic and Management, 2019)
The purpose of this study was to analyze the effect of product quality, brand image, and price perception on customer satisfaction. Research location at PT. Astra Honda Motor Gajah Mada Branch Semarang City. Research population are buyer dan user Honda Beat motorcycle at PT. Astra Honda Motor Gajah Mada Branch Semarang City are 100 people. Sampling technic using purposive sampling method are 96 people. This research using primaire data using technical data source using questionnaires and documentation. Data are be analyzed using validity, reliability, multiple regression, F detection, determination coefficient (R2), and t detection. Data processing using SPSS version 22. The results showed that the effect of product quality, brand image, and price perception had a positive and significant effect on customer satisfaction.